2023
DOI: 10.3390/biomedicines11051315
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Associations of NLRP3 Inflammasome Levels with Interleukins 1α, 1β, 33 and 37 in Adults with Prediabetes and Type 2 Diabetes Mellitus

Abstract: Inflammasome activation of the nucleotide-binding domain, leucine-rich–containing family, and pyrin domain–containing-3 (NLRP3) has been observed to be involved in the pathogenesis of numerous inflammatory diseases, including prediabetes (PD) and type 2 diabetes mellitus (T2DM). Varying levels of glycemia can trigger inflammasome activation; yet, limited studies have reported the associations between NLRP3 levels or other circulating interleukins (ILs) and glycemic status. This study investigated the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…However, the IL-1α levels significantly increased in participants who developed T2DM. This is consistent with our recent cross-sectional study, in which we found that the circulatory IL-1α levels were drastically influenced by T2DM [ 31 ]. Legiawati et al found that the IL-1α levels were higher in T2DM patients with HbA1c levels above 7% [ 32 ], while Khalil et al recorded higher serum IL-1α levels in T2DM patients infected with the hepatitis C virus [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the IL-1α levels significantly increased in participants who developed T2DM. This is consistent with our recent cross-sectional study, in which we found that the circulatory IL-1α levels were drastically influenced by T2DM [ 31 ]. Legiawati et al found that the IL-1α levels were higher in T2DM patients with HbA1c levels above 7% [ 32 ], while Khalil et al recorded higher serum IL-1α levels in T2DM patients infected with the hepatitis C virus [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are of great significance, as obesity is an important contributing factor in diabetes and this could be seen in this study, in which the weight of the PD group that developed T2DM was already higher than those of the PD group that reverted to normal and the group that remained PD. Circulatory NLRP3 is a potential inflammatory biomarker in various inflammatory diseases [ 31 , 43 ]. These results support our recent cross-sectional study [ 31 ], in which we aimed to evaluate the differences in NLRP3 inflammasomes and related ILs in a cohort of PD and T2DM participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term studies have shown that AS has a complex pathogenesis, primarily attributed to lipoprotein retention in the arterial wall and chronic inflammation ( 34 , 35 ). Hyperglycemia leads to increased inflammasome activity, upregulated nucleotide-binding oligomerization domain-like receptor 3, and ultimately elevated pro-inflammatory interleukin1β and interleukin 18 levels ( 36 ). Our study further confirms that SCAS in T2DM is a chronic inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%